Law Regarding the Status of Children Outside of Wedlock: in the Perspective of the Rights of Parents and Children - Ika Anisatul Fatma Fitria; Indryana Widi Ardhianty; Husaini, Wahyu Nurul; Dian Latifiani; Muhammad Adymas Hikal Fikri (Enigma Institute, 2023)
The Indonesian state, as stated in the 1945 Constitution, initially declared itself a legal state before undergoing amendments. After the amendment, the statement changed to